Like, Comment, and Share: Analyzing Public Sentiments of Government Policies in Social Media - Jana Flor V. Vizmanos; Sheila V. Siar; Jose Ramon G. Albert; Janina Luz C. Sarmiento; Angelo C. Hernandez (Philippine Institute for Development Studies (PIDS), 2023)
Social media has become an increasingly important tool for gauging public sentiment, offering real-time insights that can guide policy decisions. This study focuses on analyzing sentiments expressed on the Philippine Institute for Development Studies (PIDS) Facebook page, providing a window into public opinion on various development issues and governmental policies. By conducting opinion mining and sentiment analysis on comments from the top three viral Facebook posts of PIDS, which discuss education, the middle class, and social protection policies, the study reveals a range of public perspectives and highlights the challenges faced by the populace. Additionally, an online survey targeting PIDS' social media followers was conducted to understand their demographics and preferences in accessing development research. The findings demonstrate the effectiveness of social media analytics in capturing genuine public opinion, which can be instrumental in refining policies based on evidence. The study recommends enhancing analytics capabilities, systematically incorporating these insights while safeguarding data privacy, and continuously updating strategies to reflect changing public sentiments. This policy research study underscores the value of social media data in making governance more responsive and inclusive.
Keywords: 330; public sentiments; opinion mining; social media